Implementasi Business Intelligence Menggunakan Metode OLAP untuk Pengambilan Keputusan Penjualan Properti - Silitonga, Lidya Elisabet Theogracia; Hendra Suputra, I Putu Gede; Suwiprabayanti Putra, Ida Ayu Gde; Gede Suhartana, I Ketut (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 13 No 1 (2024): JELIKU Volume 13 No 1, August 2024, 2024)
Based on data from the Central Statistics Agency, population growth in Indonesia reaches 2 million – 3 million people every year. In this case, with increasing population growth, the need for housing also increases. The high demand for housing provides opportunities for property companies, one of which is PT Anugerah Indah Prima in the city of Medan. Apart from providing great opportunities, business in the property sector also has intense competition so that in order to continue to progress and develop, PT Anugerah Indah Prima must continue to be innovate in developing its business. In making a decision to develop its business, the company still faces obstacles, namely processing property sales data manually using Microsoft Excel. This data processing can not meet the needs of managers and marketing parties in making decision because the reports produced are still general information and difficult to understand.    Therefore, this research focuses on designing a dashboard that can provide insightful information in company decision making. This research utilizes business intelligence, ETL(extract, transform, and loading), OLAP(online analytical processing), and forecasting. Keywords: Information Dashboard, Business Intelligence, Property Business